Research on the prediction method of wing structure noise based on the combination of conditional generative adversarial neural network and numerical methods - Jiang, Shujie; Liang, Yuxiang; Cheng, Yu; Gao, Lingyu (Frontiers in Physics, 2024)
This paper presents a technique for predicting noise generated by airfoil structures that combines deep learning techniques with traditional numerical methods. In traditional numerical methods, accurately predicting the noise of airfoil structures requires significant computational resources, making it challenging to perform low-noise optimization design for these structures. To expedite the prediction process, this study introduces Conditional Generative Adversarial Networks (CGAN).By replacing the generator and discriminator of CGAN with traditional regression neural network models, the suitability of CGAN for regression prediction is ensured. In this study, the data computation was accelerated by expanding the kernel function in the traditional boundary element method using a Taylor series. Based on the resulting data, an alternative predictive model for wing structure noise was developed by integrating Conditional Generative Adversarial Networks (CGAN).Finally, the effectiveness and feasibility of the proposed method are demonstrated through three case studies.